Family and social experiences in children and adolescents with cancer expressed through their drawings - Olimpia Petzold; Darius Razavi (Revista Habanera de Ciencias Médicas)
Introduction: Assessing the family and social dimensions from the pediatric cancer patient's perspective encounters challenges, as children and adolescents often do not verbally express their needs and experiences related to family and interactions with others. Drawing emerges as a valuable method for psychological evaluation, offering access to the inner world of patients in an enjoyable and non-threatening manner.